The Effect of Financial Capital, Financial Technology, and Financial Behavior on MSME Performance - Helen Novita Sari; Vidi Hadyarti (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the influence of financial capital, financial technology, and financial behavior on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Sampang Regency. The method used is a quantitative method involving 50 MSME actors as research samples. Data were collected using a Likert-based questionnaire, which was designed to measure research variables systematically. The data analysis process was carried out using SPSS software. The results of the study showed that financial capital has a positive and significant influence on MSME performance. Similar things were also found in financial technology and financial behavior, where both variables had a significant positive influence on MSME performance. In addition, the results of the simultaneous test revealed that the three variables—financial capital, financial technology, and financial behavior—together had a significant influence on MSME performance in Sampang Regency. Thus, this study confirms the importance of financial and behavioral factors in supporting the success of MSMEs, especially in the research area. This conclusion provides important insights for MSME actors and policy makers to strengthen these factors in order to improve the performance of the MSME sector in Sampang Regency.